Nilai-Nilai Luhur Bagi Orang Bajo di Desa Tapi-Tapi Kecamatan Marobo Kabupaten Muna - Keke, Ahmat; Feni, Feni; Saputri, Shinta Arjunita (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
This study aims to explore and describe the Bajo people's perspectives on traditional values and how these values are implemented in their daily lives in Tapi-Tapi Village, Marobo District, Muna Regency. The research employs an ethnographic method, with data collected through participant observation and in-depth interviews. The analysis is based on Koentjaraningrat’s (1984) theory of cultural values, which emphasizes the importance of values as social guidelines within a community. The findings reveal that the Bajo community upholds deeply rooted traditional values passed down through generations. The value of responsibility is reflected in practices such as sipakkulong (mutual support in livelihood) and mapulus jamaah itu dolo modi bunang (completing assigned tasks). In terms of social care, they emphasize nggai kole sikalasa kadadarua (avoiding misunderstandings), sitabangang (mutual assistance in work), and nggai kole mangasora’dialo (avoiding destruction of the sea), which indicate strong communal and ecological awareness. Honesty is reflected in nggai kole malaponggang aha sadiri (not lying), while independence is shown in ngajama diriang (working independently). The implementation of these values is evident in various social activities, including si tuluh (mutual help), dianggo (mutual respect), sitabangang (cooperation), and bapongka (group fishing). These values not only maintain social harmony but also strengthen solidarity and cooperation within the Bajo community, especially as a coastal society dependent on marine resources.